Original paperFeasibility of virtual 3-Fr percutaneous coronary intervention using standard guiding catheters - Honda, Tsuyoshi; Fujimoto, Kazuteru; Miyao, Yuji (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction: Recent studies have reported the efficacy of sheathless percutaneous coronary intervention (PCI) using hydrophilic-coated 5-Fr guiding catheters that are one to two Fr sizes smaller in diameter than the corresponding introducer sheath (virtual 3-Fr PCI). However, the limited number of shapes of hydrophilic-coated guiding catheters occasionally makes them difficult to engage and control. Aim: To evaluate the efficacy and feasibility of virtual 3-Fr PCI using standard guiding catheters of various shapes. Material and methods: We identified 35 consecutive patients with stable angina, who underwent virtual 3-Fr PCI using either hydrophilic-coated guiding catheters (WorksTM, Medikit, Japan) or standard guiding catheters (HeartrailTM, Terumo, Japan). Results : Thirty-five patients were identified (63% men; mean age 70 ±13 years). In 2 cases, hydrophilic-coated guiding catheters were exchanged to standard guiding catheters because of difficulty in engaging the target coronary arteries. Ultimately, standard guiding catheters were used in 20 patients (57%) and hydrophilic-coated catheters were used in 15 (43%). One of 20 patients treated with standard guiding catheters and 1 of 15 treated with hydrophilic-coated guiding catheters underwent the 4-in-3 “slender mother and child” PCI technique due to difficulty of stent deployment. There were no differences between the two groups in PCI procedural variables such as procedural time, fluoroscopy time, radiation dose, or contrast dye volume. There were no access site-related complications in this study. Conclusions: These findings indicate that virtual 3-Fr PCI using standard guiding catheters is as efficient and safe as virtual 3-Fr PCI using hydrophilic-coated guiding catheters.